Punching Capacity of UHPC Post Tensioned Flat Slabs with and Without Shear Reinforcement: An Experimental Study - Ahmed Afifi; Mohamed Ramadan; Ahmed M. Farghal Maree; Ahmed M. Ebid; Amr H. Zaher; Dina M. Ors (Salehan Institute of Higher Education, 2023)
Punching capacity is one of the main items in the design of both pre-stressed and non-pre-stressed flat slabs. All international design codes include provisions to prevent this type of failure. Unfortunately, there is no code provision for UHPC yet, and hence, the aim of this research is to experimentally investigate the impact of column dimensions and punching reinforcement on the punching capacity of post-tensioned slabs and compare the results with the international design codes’ provisions to evaluate its validity. The test program included five slabs with a compressive strength of 120 MPa: one as a control sample, two to study the effect of column size, and the last two to study the effect of punching reinforcement. Comparing the results with the design codes showed that ACI-318 is more accurate with an average deviation of about 5%, while EC2 is more conservative with an average deviation of about 20%. Besides that, punching reinforcement reduces the size of the punching wedge by increasing the crack angle to 28° instead of 22° for slabs without punching reinforcement. Also, the results assure that both ductility and stiffness are enhanced with the increased column dimensions and punching reinforcement ratio. Doi: 10.28991/CEJ-2023-09-03-06 Full Text: PDF